A dam risk-removing reinforcement material and reinforcement method

By using glass fiber, polymethyl methacrylate microspheres and layered bentonite in the dam hazard removal and reinforcement materials, a network structure is formed, which solves the problem of slow development of dam strength and prone to cracks, and improves the dam compressive strength and leak resistance.

CN116120014BActive Publication Date: 2024-12-13SHANDONG WATER GENERAL CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202310108088.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-14
Publication Date
2024-12-13
Estimated Expiration
2043-02-14

AI Technical Summary

Technical Problem

The strength of existing dam hazard removal and reinforcement materials develop slowly during use, and are prone to cracks, affecting the anti-leakage performance.

Method used

The dam hazard-reinforcement material consisting of cement, anti-cracking agents, auxiliary agents, etc. is used to form a mesh structure to enhance the resistance of the material through the combination of glass fibers, polymethyl methacrylate microspheres, layered bentonite and other components. Compression strength and compactness reduce the generation of cracks.

Benefits of technology

It improves the crack resistance and leakage resistance of the dam hazard removal and reinforcement materials, extends the service life of the dam, reduces the occurrence of cracks, and enhances the overall strength of the dam.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to the field of dam hazard removal and reinforcement materials, and specifically discloses a dam hazard removal and reinforcement material and a reinforcement method. The dam hazard removal and reinforcement material of the present application is mainly made of the following raw materials: cement, water, water reducing agent, air entraining agent, coarse aggregate, fine aggregate, anti-cracking agent, auxiliary agent, and quick-setting agent. The anti-cracking agent is at least two of glass fiber, polymethyl methacrylate microspheres, and layered bentonite, and the auxiliary agent is composed of steel slag and slag; the reinforcement method uses the above-mentioned dam hazard removal and reinforcement material for dam hazard removal and reinforcement, including the following steps: mixing cement, water, water reducing agent, air entraining agent, coarse aggregate, fine aggregate, anti-cracking agent, auxiliary agent, and quick-setting agent to obtain the dam hazard removal and reinforcement material; performing high-pressure jet grouting according to the conventional high-pressure jet grouting method, and spraying the dam hazard removal and reinforcement material to the dam reinforcement and repair position. The dam hazard removal and reinforcement material of the present application has strong anti-cracking performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of dam hazard removal and reinforcement materials, and more specifically, to a dam hazard removal and reinforcement material and a reinforcement method. Background Art

[0002] Water conservancy projects are an important part of my country's infrastructure projects. Through the construction of water conservancy projects, we can achieve the rational use of water resources, effectively prevent floods and waterlogging disasters, and better meet the needs of social production and people's daily life for water resources. As the core structure of water conservancy projects, the dam itself accounts for 80%-90% of the total water conservancy projects. Therefore, it is very important to do a good job in dam construction during the construction of water conservancy projects.

[0003] The dam was built a long time ago and has been in operation for a long time. Coupled with maintenance and management issues, the dam has certain leakage problems, which pose a threat to the operation of the water conservancy project.

[0004] At present, the technologies for reinforcing dams generally include horizontal anti-seepage reinforcement technology, high-pressure jet grouting technology, vibration sinking mold anti-seepage technology, etc. Among them, the high-pressure jet grouting technology uses the jet effect to change the structure of the stratum where the dam is located, and then pours in cement-based grouting materials to form a condensate inside the stratum, thereby achieving the effect of anti-seepage reinforcement.

[0005] The dam reinforcement material is generally cement-based grouting material, which is a grouting material formed by adding appropriate amount of mineral admixtures and admixtures with cement as the main gelling material. The current cement-based grouting material develops strength slowly during use and may crack during use. Summary of the invention

[0006] In order to improve the anti-cracking performance of dam hazard removal and reinforcement materials, the present application provides a dam hazard removal and reinforcement material and a reinforcement method.

[0007] In the first aspect, the present application provides a dam risk removal and reinforcement material, which adopts the following technical solution:

[0008] A dam hazard removal and reinforcement material is mainly made of the following raw materials in parts by weight: 130-200 parts of cement, 60-80 parts of water, 1-2 parts of water reducer, 0.3-0.5 parts of air entraining agent, 350-400 parts of coarse aggregate, 250-280 parts of fine aggregate, 2-4 parts of anti-cracking agent, 1-2 parts of auxiliary agent, and 1-2 parts of quick-setting agent, wherein the anti-cracking agent is at least two of glass fiber, polymethyl methacrylate microspheres, and layered bentonite, and the auxiliary agent is composed of steel slag and ore slag in a mass ratio of (5-8):(3-4).

[0009] Preferably, the addition of glass fiber facilitates the reduction of the dam risk prevention and reinforcement material structure.

[0010] Preferably, adding steel slag to the dam hazard removal and reinforcement materials can effectively promote crack healing.

[0011] Preferably, the average length of the glass fibers is 15-20 mm.

[0012] By adopting the above technical scheme, the steel slag and slag in the auxiliary agent cooperate with each other, the steel slag powder has a certain hydration activity, the hydration of the steel slag powder can stimulate and promote the hydration reaction of the slag powder, the steel slag powder is hydrated to generate CSH gel, the slag powder is hydrated to generate calcium vanadium, the CSH gel and the calcium vanadium form a network structure, which is helpful to improve the strength of the dam risk removal and reinforcement materials, and at the same time, the steel slag and slag have certain gelling properties, which are convenient for coordinated cooperation with cement to improve the connection stability between the various parts of the dam risk removal and reinforcement materials, and at the same time, improve the density and strength of the dam risk removal and reinforcement materials, and the addition of the anti-cracking agent is convenient to reduce the dam risk removal and reinforcement materials. The glass fiber in the anti-cracking agent is convenient for improving the crack resistance of the dam reinforcement material when it is subjected to load. The glass fiber distributed in the dam reinforcement material plays a bridging role, hindering the generation and expansion of cracks; the polymethyl methacrylate microspheres are easier to enter the microcracks inside the dam reinforcement material, and cooperate with the layered bentonite to fill the microcracks, while improving the density of the dam reinforcement material, thereby improving the compressive strength of the dam reinforcement material and reducing the probability of cracks when the dam reinforcement material is subjected to pressure.

[0013] Preferably, the mass ratio of the anti-cracking agent to the auxiliary agent is (2.5-3.5): (1.2-1.5).

[0014] By adopting the above-mentioned technical scheme, the mass ratio of the anti-cracking agent and the auxiliary agent is adjusted to make the mass ratio of the anti-cracking agent and the auxiliary agent reach the best. After testing, the inventors of the present application found that when the anti-cracking agent and the auxiliary agent are within the above-mentioned range, it is convenient to improve the connection strength between the anti-cracking agent and other components of the dam hazard removal and reinforcement material, so as to better play the role of the anti-cracking agent and the auxiliary agent, thereby improving the anti-cracking effect of the dam hazard removal and reinforcement material.

[0015] Preferably, the steel slag powder is modified steel slag powder, and the preparation method of the modified steel slag powder comprises the following steps: S1, pretreatment of steel slag: grinding the steel slag and mixing it with a pore-forming agent to obtain steel slag slurry, vibrating the steel slag slurry, performing heat curing, roasting, and cooling to obtain pretreated steel slag, wherein the pore-forming agent is composed of sodium hydroxide and acrylic resin emulsion in a mass ratio of (3-4): (0.1-0.2); S2, preparation of modified steel slag powder: mixing the pretreated steel slag with a Na2SO4 / SiO2 complex and drying to obtain modified steel slag powder.

[0016] Preferably, the container for curing in step S1 is a constant temperature drying oven, and the curing is divided into a first stage and a second stage. The curing time of the first stage is 5-6 hours, and the curing temperature is 50-60°C. The curing time of the second stage is 20-26 hours, and the curing temperature is 20-30°C. The roasting temperature is 400-500°C, and the roasting time is 3-5 hours.

[0017] Preferably, the drying temperature in step S2 is 70-80°C, the drying time is 20-25h, the drying container is a vacuum drying oven, and after drying, it is washed with anhydrous ethanol. The mass ratio of the pretreated steel slag to the Na2SO4 / SiO2 composite is (8-10):(1-3).

[0018] Preferably, the preparation method of the Na2SO4 / SiO2 composite comprises the following steps: (1) preparing raw materials: crushing the raw materials and passing through a 250-mesh sieve with a sieve residue of no more than 0.5% to achieve the required fineness; (2) preparing raw materials: mixing SiO2: Na2SO4: ceramic pore-forming agent in a ratio of 40:60:10; (3) granulation: uniformly mixing the prepared raw materials, adding 3% sodium carboxymethyl cellulose for granulation; (4) dry pressing: setting the maximum pressure to 70 MPa, and slowly increasing the pressure and maintaining the pressure for 1 min; (5) drying: setting the maximum temperature to 110°C, the drying time to 3.5 h and reaching constant weight; (6) sintering: the heating rate is 4°C / min, and the maximum sintering temperature is 1000°C.

[0019] By adopting the above technical scheme, the steel slag powder is pretreated and mixed with the pore-forming agent, so as to adjust the pore structure of the steel slag and make the pore size of the steel slag more uniform. At the same time, after the steel slag powder is treated with the pore-forming agent, the pretreated steel slag powder appears honeycomb-shaped, which is convenient for better loading of Na2SO4 / SiO2 complex. The Na2SO4 / SiO2 complex has the effect of phase change heat storage, which is convenient for reducing the temperature rise too fast during the hydration process of the dam hazard removal and reinforcement material, so as to further reduce the resistance of the dam hazard removal and reinforcement material to cracking.

[0020] Preferably, the mass ratio of the pretreated steel slag to the Na2SO4 / SiO2 composite is (8-10):(1-3).

[0021] By adopting the above technical scheme, the mass ratio of pretreated steel slag and Na2SO4 / SiO2 composite is adjusted to achieve the best mass ratio. The pretreated steel slag has a rich pore structure, and the Na2SO4 / SiO2 composite has heat storage properties, which may control the temperature changes caused by the early hydration heat of cement inside the dam hazard removal and reinforcement materials, improve the strength of the dam hazard removal and reinforcement materials, and reduce the occurrence of cracks in the dam hazard removal and reinforcement materials.

[0022] Preferably, the anti-cracking agent is composed of glass fiber, polymethyl methacrylate microspheres, and layered bentonite in a mass ratio of (5-7):(2-3):(2-3).

[0023] By adopting the above technical scheme, the ratio of the three components of glass fiber, polymethyl methacrylate microspheres and layered bentonite is adjusted to achieve the best ratio of the three components. Among them, the addition of glass fiber facilitates further close connection with the matrix of the dam hazard removal and reinforcement material, further improves the compressive strength of the dam hazard removal and reinforcement material, and enhances the anti-cracking performance of the dam hazard removal and reinforcement material. At the same time, it cooperates with the layered bentonite to form a network structure under the action of cement and auxiliary agents; the bentonite distributed under the network structure swells when it encounters water; the polymethyl methacrylate microspheres are spherical The polymer particles with a shape and a particle size ranging from tens of nanometers to hundreds of microns have a small specific surface area due to their small particle size, which helps to increase the bonding area between the polymer microspheres and other raw materials. In addition, the small size makes it easier for the polymethyl methacrylate microspheres to enter the microcracks inside the dam disaster prevention and reinforcement material, which helps to fill the microcracks, thereby helping to improve the density of the anti-cracking dam disaster prevention and reinforcement material, which is beneficial to improving the compressive performance of the anti-cracking dam disaster prevention and reinforcement material, thereby reducing the probability of cracks in the dam disaster prevention and reinforcement material when subjected to pressure.

[0024] Preferably, the glass fiber is a modified glass fiber, and the preparation method of the modified glass fiber comprises the following steps: S1, preparation of pretreated glass fiber: mixing the glass fiber with a binder to obtain pretreated glass fiber; the binder is composed of sodium alginate and gum arabic in a mass ratio of (3-5): (1-2); S2, preparation of microcapsules: mixing bentonite, Bacillus pasteurianus, a swelling agent, and PVA powder to obtain a mixture, spraying a PVA aqueous solution on the surface of the mixture, and drying to obtain the microcapsule.

[0025] Preferably, the PVA solution is a 1% by mass PVA aqueous solution, which is commercially available.

[0026] Preferably, the mass ratio of the PVA aqueous solution to the mixed material is (8-10):1.

[0027] Preferably, the particle size of the PVA powder is 100 mesh.

[0028] Preferably, the drying is carried out in a drying oven at a drying temperature of 100-110°C.

[0029] Preferably, the mass ratio of the bentonite, Bacillus pasteurianus, the swelling agent, and the PVA powder is (10-20):(50-60):(5-10):(1-5). The swelling agent is an ettringite swelling agent. The Bacillus pasteurianus is commercially available.

[0030] By adopting the above technical scheme, the microcapsule can protect the internal Bacillus pasteurianus. When fine cracks appear in the dam, the capsule wall will automatically rupture under pressure, releasing the internal microorganism Bacillus pasteurianus. The incoming air and moisture will cause the Bacillus pasteurianus to germinate and restore the mineralization activity. The microorganisms will continuously induce the generation of calcium carbonate precipitation for filling. Bentonite has a porous structure. Based on capillary action, it absorbs a large amount of water, which leads to volume expansion. The expansion agent has the effect of expansion and densification, which is convenient for improving the strength of the dam disaster prevention and reinforcement materials. The synergistic combination of bentonite, Bacillus pasteurianus, expansion agent, and PVA powder can further reduce the occurrence of cracks and, at the same time, reduce the area of ​​cracks.

[0031] Preferably, the particle size distribution of the polymethyl methacrylate microspheres is 70-80nm accounting for 30-35% by mass, 80-100nm accounting for 25-35% by mass, 100-120nm accounting for 25-30% by mass, and 120-150nm accounting for 10-25% by mass.

[0032] By adopting the above technical scheme, the particle size of the polymethyl methacrylate microspheres is adjusted, and a variety of particle sizes are used to facilitate the distribution of the polymethyl methacrylate microspheres in positions of different pore sizes of the dam hazard removal and reinforcement materials. On the one hand, it is convenient to improve the strength of the dam hazard removal and reinforcement materials, and on the other hand, it is convenient to increase the distribution area of ​​the polymethyl methacrylate microspheres, so as to better play the role of the polymethyl methacrylate microspheres, so as to further improve the situation of cracks in the dam.

[0033] Preferably, 0.1-0.5 parts of microsilica powder are also included.

[0034] By adopting the above technical scheme, the addition of microsilica powder facilitates further filling of cracks in the dam hazard removal and reinforcement materials, improves the density of the dam hazard removal and reinforcement materials, and may further reduce the generation of cracks. The seed effect, volcanic ash effect and micro-aggregate filling effect of microsilica powder and the relatively highly active alumina tetrahedron in the slag can synergistically enhance the hydration reaction in the highly alkaline liquid phase system of steel slag, so that more CSH gel and AFt crystals are generated in the composite cementitious system. The CSH gel tightly wraps the AFt crystals, and the two grow in an interlaced manner to form a complex and dense network structure, thereby improving the mechanical properties of the cementitious material. Steel slag and slag powder have a synergistic effect. The hydration reaction of slag can promote the continuous hydration of steel slag to a certain extent. The synergistic effect of the two rapidly increases the number of hydration products in the later stage of the reaction.

[0035] Preferably, the microsilica powder is modified microsilica powder, and the preparation method of the modified microsilica powder comprises the following steps: mixing the microsilica powder with an aqueous ethanol solution, an oxalic acid solution and a silane coupling agent, heating in a water bath to obtain a microsilica powder emulsion, and centrifuging, washing and drying the microsilica powder emulsion.

[0036] Preferably, the volume ratio of the ethanol-water solution is 1:1.

[0037] Preferably, the pH value during the preparation of the modified microsilica powder is 4-4.5.

[0038] Preferably, the mass ratio of the microsilica powder to the silane coupling agent is 8:3.

[0039] Preferably, the drying temperature is 60-70° C. and the drying time is 10-12 hours.

[0040] Preferably, the silane coupling agent is KH-750.

[0041] By adopting the above technical scheme, the silane coupling agent is coated on the surface of the microsilica powder, so that the hydrogen bonding and surface tension between the microsilica powder particles are reduced, the agglomeration phenomenon between the microsilica powder particles is reduced, the dispersibility of the microsilica powder is improved, and the microsilica powder is easier to react with the auxiliary agent, so as to further improve the anti-cracking performance of the dam hazard removal and reinforcement material.

[0042] In the second aspect, the present application provides a method for dam risk removal and reinforcement, which adopts the following technical solution:

[0043] A dam risk removal and reinforcement method, using the dam risk removal and reinforcement material for dam risk removal and reinforcement, comprises the following steps:

[0044] (1) Raw material mixing: Mix cement, water, water reducing agent, air entraining agent, coarse aggregate, fine aggregate, anti-cracking agent, auxiliary agent and quick-setting agent to obtain dam hazard removal and reinforcement materials;

[0045] (2) Repair: Perform high-pressure jet grouting according to a conventional high-pressure jet grouting method to spray the dam hazard removal and reinforcement material obtained in step (1) onto the dam reinforcement and repair location.

[0046] Preferably, the conditions for high-pressure spraying in step (2) are: high-pressure water pressure of 30-35 MPa, flow rate of 55-70 L / min; compressed air pressure of 0.8 MPa, flow rate of 1.5 m / min. 3 / min, the pressure of the reinforcement slurry is 0.15-0.2Mpa, and the flow rate is 80L / min.

[0047] By adopting the above technical scheme, in the process of dam hazard removal and reinforcement of the present application, the dam hazard removal and reinforcement material prepared by the present application is used, which has a short setting time, good mechanical properties, and is not prone to cracking.

[0048] In summary, this application has the following beneficial effects:

[0049] 1. The dam hazard removal and reinforcement material of the present application contains an accelerator, an anti-cracking agent, and an auxiliary agent. The auxiliary agent works together with cement to further improve the gelling effect of cement. The glass fiber in the anti-cracking agent facilitates improving the crack resistance of the dam hazard removal and reinforcement material when it is subjected to load. The polymethyl methacrylate microspheres can more easily enter the microcracks inside the dam hazard removal and reinforcement material, and cooperate with the layered bentonite to fill the microcracks, thereby improving the strength of the reinforced dam and reducing the occurrence of cracks in the repaired dam.

[0050] 2. The dam hazard removal and reinforcement material of the present application modifies the steel slag powder and loads the Na2SO4 / SiO2 complex with heat storage function on the steel slag powder, so as to reduce the problem of rapid temperature change caused by cement hydration and further reduce cracks in the repaired dam. DETAILED DESCRIPTION

[0051] The present application is further described in detail below with reference to the embodiments.

[0052] The glass fiber of the present application is an alkali-resistant glass fiber, and the length of the glass fiber is 2-5 cm and the diameter is 0.5-1.5 mm.

[0053] The steel slag in this application is a silicon-aluminum industrial waste, and the steel slag particle size is 400-500 kg / m 2 .

[0054] The slag in this application is a silicon-aluminum industrial waste, and the steel slag particle size is 400-500 kg / m 2 .

[0055] The quick-setting agent of the present application is an alkali-free liquid quick-setting agent.

[0056] The air entraining agent of the present application is sodium rosinate.

[0057] The particle size of the microsilica powder of the present application is 0.1-0.15 μm, and the content of silicon dioxide is not less than 85%. Example

[0058] Embodiment 1: A dam hazard removal and reinforcement material, the raw material composition ratio is shown in Table 1, wherein the cement is P042.5R; the water reducer is a polycarboxylic acid high-efficiency water reducer; the fine aggregate is natural fine sand with a fineness modulus of 2.2 and a mud content of <1.0%; the coarse aggregate is crushed stone with a particle size of 5-20 mm and continuous grading; the anti-cracking agent is composed of glass fiber and polymethyl methacrylate microspheres in a mass ratio of 1:1, and the auxiliary agent is composed of steel slag and slag in a mass ratio of 5:8, and the particle size of the polymethyl methacrylate microspheres is 80 nm.

[0059] A dam risk removal and reinforcement method, using the dam risk removal and reinforcement material for dam risk removal and reinforcement, comprises the following steps:

[0060] (1) Raw material mixing: Mix cement, water, water reducing agent, air entraining agent, coarse aggregate, fine aggregate, anti-cracking agent, auxiliary agent and quick-setting agent to obtain dam hazard removal and reinforcement materials;

[0061] (2) Repair: Perform high-pressure jet grouting according to the conventional high-pressure jet grouting method, and spray the dam risk prevention and reinforcement material obtained in step (1) to the dam reinforcement and repair position, wherein the conditions for high-pressure jetting are: high-pressure water pressure of 35MPa, flow rate of 60L / min; compressed air pressure of 0.8MPa, flow rate of 1.5m 3 / min, the pressure of the reinforcement slurry is 0.2Mpa and the flow rate is 80L / min.

[0062] Table 1: Raw material composition ratio of examples 1-5 dam risk prevention and reinforcement materials

[0063]

[0064]

[0065] Example 2-4: A dam hazard removal and reinforcement material, the raw material composition ratio is as shown in Table 1, and the difference from Example 1 is that the raw material composition ratio is different.

[0066] Example 5: A dam hazard removal and reinforcement material, the raw material composition ratio is shown in Table 1, and the difference from Example 4 is that microsilica powder is also added.

[0067] Embodiment 6: A dam hazard removal and reinforcement material, which is different from Embodiment 5 in that: the steel slag powder is modified steel slag powder, and the preparation method of the modified steel slag powder comprises the following steps: S1, pre-treating the steel slag: grinding the steel slag and mixing it with a pore-forming agent to obtain a steel slag slurry, vibrating the steel slag slurry, performing heat curing, roasting, and cooling to obtain the pre-treated steel slag, wherein the pore-forming agent is composed of sodium hydroxide and acrylic resin emulsion in a mass ratio of 3:0.2; wherein the curing container is a constant temperature drying oven, and the curing is divided into a first stage and a second stage, and the first stage The first stage curing time is 6h, the curing temperature is 60℃, the second stage curing time is 24h, the curing temperature is 30℃; the roasting temperature is 450℃, and the roasting time is 4h; S2, the pretreated steel slag is mixed with the Na2SO4 / SiO2 complex, and after drying, the modified steel slag powder is obtained, wherein the drying temperature is 80℃, the drying time is 23h, the drying container is a vacuum drying oven, and after drying, it is washed with anhydrous ethanol. The mass ratio of the pretreated steel slag to the Na2SO4 / SiO2 complex is 10:3.

[0068] Example 7: A dam hazard removal and reinforcement material, which differs from Example 6 in that the anti-cracking agent is composed of glass fiber, polymethyl methacrylate microspheres, and layered bentonite in a mass ratio of 5:2:2.

[0069] Example 8: A dam hazard removal and reinforcement material, which differs from Example 6 in that the anti-cracking agent is composed of glass fiber, polymethyl methacrylate microspheres, and layered bentonite in a mass ratio of 7:3:3.

[0070] Embodiment 9: A dam hazard removal and reinforcement material, which is different from Embodiment 8 in that: the glass fiber is a modified glass fiber, and the preparation method of the modified glass fiber comprises the following steps: S1, preparation of pretreated glass fiber: mixing the glass fiber with a binder to obtain pretreated glass fiber; the binder is composed of sodium alginate and gum arabic in a mass ratio of 5:2; S2, preparation of microcapsules: mixing bentonite, Bacillus pasteurianus, a swelling agent, and PVA powder to obtain a mixture, spraying the PVA aqueous solution on the surface of the mixture, and drying. The PVA solution is a PVA aqueous solution with a mass fraction of 1%, which is commercially available. The mass ratio of the PVA aqueous solution to the mixture is 10:1. The particle size of the PVA powder is 100 mesh. Drying is carried out in a drying oven at a drying temperature of 110°C. The mass ratio of bentonite, Bacillus pasteurianus, a swelling agent, and PVA powder is 20:50:10:2. The swelling agent is an ettringite swelling agent. Bacillus pasteurianus is commercially available.

[0071] Example 10: A dam hazard removal and reinforcement material, which differs from Example 9 in that: the particle size gradation of the polymethyl methacrylate microspheres is 70-80nm (35% by mass), 80-100nm (25% by mass), 100-120nm (30% by mass), and 120-150nm (10% by mass).

[0072] Embodiment 11: A dam hazard removal and reinforcement material, which differs from Embodiment 10 in that the microsilica powder is modified microsilica powder, and the preparation method of the modified microsilica powder comprises the following steps: mixing the microsilica powder with an ethanol aqueous solution, an oxalic acid solution and a silane coupling agent, heating in a water bath to obtain a microsilica powder emulsion, centrifuging the microsilica powder emulsion, washing and drying. The volume ratio of the ethanol aqueous solution is 1:1. The pH value during the preparation of the modified microsilica powder is 4.5. The mass ratio of microsilica powder to silane coupling agent is 8:3. The drying temperature is 70°C and the drying time is 12 hours. The silane coupling agent is KH-750.

[0073] Comparative Example 1: A dam hazard removal and reinforcement material, which differs from Example 1 in that no anti-cracking agent is added.

[0074] Comparative Example 2: A dam hazard removal and reinforcement material, which differs from Example 1 in that the anti-cracking agent is glass fiber.

[0075] Anti-cracking performance test: The dam hazard removal and reinforcement materials prepared in Examples 1-11 and Comparative Examples 1-2 were taken and calculated according to GB / T50081-2016 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete". The number of cracks per unit area and the total crack area per unit area were measured 24 hours after the dam hazard removal and reinforcement materials were poured. The test results are shown in Table 2.

[0076] Compressive strength test: The compressive strength of the dam hazard removal and reinforcement materials prepared in Examples 1-11 and Comparative Examples 1-2 was tested with reference to the test method in GB / T50081-2016 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete". The test results are shown in Table 2.

[0077] Table 2 Performance test results of dam risk prevention and reinforcement materials of Examples 1-11 and Comparative Examples 1-2

[0078]

[0079] In combination with Examples 1-4 and the data in Table 2, it can be seen that by adjusting the ratio of each component of the dam hazard removal and reinforcement material, and under the proportion of the present application, the compressive strength, number of cracks and cracking area of ​​the dam hazard removal and reinforcement material are better.

[0080] In combination with Examples 4-5 and the data in Table 2, it can be seen that the compressive strength, number of cracks and cracked area of ​​the dam hazard removal reinforcement material prepared in Example 5 are better than the compressive strength, number of cracks and cracked area of ​​the dam hazard removal reinforcement material prepared in Example 4. The difference between Example 5 and Example 4 is that a small amount of microsilica powder is added to Example 5. The inventor of the present application speculates that the addition of microsilica powder may cooperate with other components in the dam hazard removal reinforcement material to increase the compressive strength of the dam hazard removal reinforcement material and reduce the number of cracks and cracked area of ​​the dam hazard removal reinforcement material.

[0081] In combination with Examples 5-6 and the data in Table 2, it can be seen that the compressive strength of the dam hazard removal reinforcement material prepared in Example 6 is better than the compressive strength of the dam hazard removal reinforcement material prepared in Example 5, and the number of cracks in the dam hazard removal reinforcement material prepared in Example 6 is less. The difference between Example 6 and Example 5 is that the steel slag powder in Example 6 is modified steel slag powder. The inventor of the present application speculates that the steel slag powder is modified, and the modified steel slag powder has a heat storage effect, which may reduce the increase in heat during the solidification process of the dam hazard removal reinforcement material, thereby reducing the cracks caused by temperature, and may reduce the number of cracks and reduce the crack area of ​​the cracks.

[0082] In combination with Examples 6-8, Comparative Example 2, and the data in Table 2, it can be seen that the compressive strength, number of cracks, and crack area of ​​the dam hazard removal reinforcement materials prepared in Examples 7-8 are better. The inventors of the present application speculate that when the anti-cracking agent is compounded with three components of glass fiber, polymethyl methacrylate microspheres, and layered bentonite, these three components cooperate with each other or these three components may cooperate with other materials of the dam hazard removal reinforcement material to improve the performance of the prepared dam hazard removal reinforcement material.

[0083] In combination with Examples 8-9 and the data in Table 2, it can be seen that the dam hazard removal and reinforcement material produced in Example 9 has fewer cracks and a smaller crack area. The difference between Example 9 and Example 8 is that Example 9 modifies the glass fiber so that microcapsules containing a repair agent are adhered to the outer layer of the glass fiber. The inventor of the present application speculates that the glass fiber drives the microcapsules to be distributed in the dam hazard removal and reinforcement material, which may increase the distribution area of ​​the microcapsules. At the same time, the microcapsules are also distributed on the mesh structure of the glass fiber, which is convenient for reducing the number of cracks and shrinking the crack area.

[0084] In combination with Examples 9-10 and the data in Table 2, it can be seen that the compressive strength of the dam hazard removal reinforcement material prepared in Example 10 is better than the compressive strength of the dam hazard removal reinforcement material prepared in Example 9. The difference between Example 10 and Example 9 is that Example 10 uses polymethyl methacrylate microspheres of different particle sizes. The inventor of the present application speculates that polymethyl methacrylate microspheres of different particle size gradations are distributed in the dam hazard removal reinforcement material, which may fill the pores of the dam hazard removal reinforcement material, increase the density of the dam hazard removal reinforcement material, and thereby improve the compressive strength of the dam hazard removal reinforcement material.

[0085] In combination with Examples 10-11 and the data in Table 2, it can be seen that the dam hazard removal reinforcement material prepared in Example 11 has better compressive strength, number of cracks and crack area than the dam hazard removal reinforcement material prepared in Example 10, and the difference between Example 11 and Example 10 is that the microsilica powder in Example 11 has been modified. The inventors of the present application speculate that modifying the microsilica powder and improving the dispersion of the microsilica powder in the dam hazard removal reinforcement material may increase the density of the dam hazard removal reinforcement material, thereby improving the compressive strength of the dam hazard removal reinforcement material.

[0086] In combination with Example 1, Comparative Example 1, and the data in Table 2, it can be seen that the performance of the dam hazard removal reinforcement material prepared in Example 1 is better than that of the dam hazard removal reinforcement material prepared in Comparative Example 1 in all aspects. The inventor of the present application speculates that the addition of anti-cracking agent has a greater impact on the performance of the dam hazard removal reinforcement material, and may improve the compressive strength and crack resistance of the dam hazard removal reinforcement material.

[0087] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A dam risk removal and reinforcement material, characterized in that: It is mainly made of the following raw materials in parts by weight: 130-200 parts of cement, 60-80 parts of water, 1-2 parts of water reducer, 0.3-0.5 parts of air entraining agent, 350-400 parts of coarse aggregate, 250-280 parts of fine aggregate, 2-4 parts of anti-cracking agent, 1-2 parts of auxiliary agent, 1-2 parts of accelerating agent, and 0.1-0.5 parts of microsilica powder; The anti-cracking agent is composed of glass fiber, polymethyl methacrylate microspheres, and layered bentonite in a mass ratio of (5-7):(2-3):(2-3); The glass fiber is a modified glass fiber. The preparation method of the modified glass fiber comprises the following steps: S1, preparation of pretreated glass fiber: mixing the glass fiber with a binder to obtain pretreated glass fiber; the binder is composed of sodium alginate and gum arabic in a mass ratio of (3-5): (1-2); S2, preparation of microcapsules: mixing bentonite, Bacillus pasteurianus, a swelling agent, and PVA powder to obtain a mixture, spraying a PVA aqueous solution on the surface of the mixture, and drying to obtain the microcapsules; The auxiliary agent is composed of steel slag and ore slag in a mass ratio of (5-8):(3-4); The steel slag is modified steel slag powder. The preparation method of the modified steel slag powder comprises the following steps: S1, pre-treating the steel slag: grinding the steel slag and mixing it with a pore-forming agent to obtain a steel slag slurry, vibrating the steel slag slurry, performing heat curing, roasting, and cooling to obtain the pre-treated steel slag, wherein the pore-forming agent is composed of sodium hydroxide and acrylic resin emulsion in a mass ratio of (3-4): (0.1-0.2); S2, preparing the modified steel slag powder: mixing the pre-treated steel slag with a Na2SO4 / SiO2 complex and drying to obtain the modified steel slag powder; The preparation method of the Na2SO4 / SiO2 composite comprises the following steps: (1) preparing raw materials: crushing the raw materials and passing through a 250-mesh sieve with a sieve residue of no more than 0.5% to achieve the required fineness; (2) preparing raw materials: mixing SiO2:Na2SO4:ceramic pore-forming agent in a ratio of 40:60:10; (3) granulation: uniformly mixing the prepared raw materials, adding 3% sodium carboxymethyl cellulose for granulation; (4) dry pressing: setting the maximum pressure to 70 MPa, and slowly increasing the pressure and maintaining the pressure for 1 min; (5) drying setting: the maximum temperature is 110°C, the drying time is 3.5 h, and constant weight is reached; (6) sintering: the heating rate is 4°C / min, and the maximum sintering temperature is 1000°C; The microsilica powder is modified microsilica powder. The preparation method of the modified microsilica powder comprises the following steps: mixing the microsilica powder with an ethanol aqueous solution, an oxalic acid solution and a silane coupling agent, heating the mixture in a water bath to obtain a microsilica powder emulsion, and centrifuging, washing and drying the microsilica powder emulsion.

2. A dam risk elimination and reinforcement material according to claim 1, characterized in that: The mass ratio of the anti-cracking agent to the auxiliary agent is (2.5-3.5):(1.2-1.5).

3. The dam risk elimination and reinforcement material according to claim 1, characterized in that: The mass ratio of the pretreated steel slag to the Na2SO4 / SiO2 composite is (8-10):(1-3).

4. The dam risk elimination and reinforcement material according to claim 1, characterized in that: The particle size distribution of the polymethyl methacrylate microspheres is 70-80nm (30-35% by mass), 80-100nm (25-35% by mass), 100-120nm (25-30% by mass), 120-150nm (10-25% by mass), and the sum of the mass proportions of each particle size distribution is 100%.

5. A method for strengthening a dam, characterized in that: The dam risk removal and reinforcement material according to any one of claims 1 to 4 is used for dam risk removal and reinforcement, comprising the following steps: (1) Raw material mixing: Mix cement, water, water reducing agent, air entraining agent, coarse aggregate, fine aggregate, anti-cracking agent, auxiliary agent and quick-setting agent to obtain dam hazard removal and reinforcement materials; (2) Repair: Perform high-pressure jet grouting according to a conventional high-pressure jet grouting method to spray the dam hazard removal and reinforcement material obtained in step (1) onto the dam reinforcement and repair location.

Citation Information

Patent Citations

  • Method of synthesizing monodisperse micron-level poly(methyl methacrylate) micro-sphere

    CN101054427A

  • Low-shrinkage crack self-compacting concrete

    CN103435306A

  • Preparation method for high-temperature phase change energy storage concrete

    CN105621987A

  • Cement-based grouting material and grouting mortar

    CN108164222A

  • Dam danger eliminating and reinforcing material and reinforcing method thereof

    CN110627472A